168 Asymptomatic dengue illness complicated by Guillain Barre syndrome. Issue 6 (27th May 2022) - Siddiqui, Sarah; Midgley, Laura; Poole, Olivia; Redmond, Ian; Alkufri, Fadi; Harikrishnan, Sreedharan; Moran, Nicholas
Abstract : Arboviral infection Dengue can cause a spectrum of disease varying from asymptomatic illness to dengue fever to the severe dengue hemorrhagic fever. Neurological complications are rarely reported in the lit- erature (0.5–6%), mostly from dengue-endemic areas in tropics and subtropical regions. We report a case of a 59-year-old man who returned from a recent work-related travel from India. Three weeks following a mild viral prodrome, he developed bilateral lower motor neuron facial palsy with absent deep tendon reflexes. CSF showed albuminocytologic dissociation and electrophysiological studies showed demyeli- nating neuropathy. Routine GBS screen for common etiological viruses was negative and subsequently additional testing based on recent travel was performed which showed positive Dengue IgM and RNA in serum. The patient was treated with plasma exchange for 5 days and his facial weakness improved to a great extent. This case demonstrates the importance of considering arboviral infections such as Dengue in patients with GBS particularly in people living in or travelling from endemic areas. Additionally, like many other viral illnesses, there may not be clear clinical evidence of Dengue fever and the prodrome may go unnoticed and undiagnosed, hence a high index of suspicion is required. s_hasan_s@yahoo.com